Compensation for moral damages for violation of police officer’s personal non-property rights: problems of law enforcement (Law and Safety, 2023)
The article is devoted to the study of legislation and legal doctrine on compensation for moral damages for humiliation of honour, dignity and the right to inviolability of business reputation of a police officer who is a representative of law enforcement agencies. It has been determined that the institute of civil liability distinguishes compensation for moral damages as a specific measure of civil liability, which is specified in the Civil Code of Ukraine as a measure of protection. It has been established that the amount of moral damages cannot be calculated by the court when deciding on their compensation, and therefore the court is guided by its own subjective beliefs when calculating them, which is a problem of law enforcement. Case law on police officers' claims for moral damages from persons who have violated their personal non-property rights has been analysed. It has been found that the courts apply the practice of higher courts, which is based on the approaches of the international community, that a police officer is a public figure whose activities are of public interest and therefore must tolerate criticism, and this cannot be a ground for going to court. It has been substantiated that an employee of an internal affairs agency is a representative of the State, and therefore, in case of violation of his/her personal non-property rights, in particular, the right to inviolability of business reputation, failure to award him/her compensation for moral damages affects the reputation of both the agency in which he/she serves and the State. It has been proven that this approach of binding a police officer to the provisions on public figures harms the reputation of the State and eliminates the application of the preventive function of civil liability, which is an important factor for maintaining public order. To support the positions of national scholars, the author proposes to create a separate regulatory act which would provide guarantees for the protection of personal non-property rights of law enforcement officers and establish a balance between the observance of freedom of expression in the media regarding police activities and the observance of the rights of law enforcement officers in the performance of their official duties.
Keywords: civil liability; moral damages; internal affairs bodies; law enforcement activity; personal non-property rights; honour; dignity; business reputation.